First total synthesis and phytotoxic activity of Streptomyces sp. metabolites abenquines. Issue 16 (20th April 2016) - Nain-Perez, Amalyn; Barbosa, Luiz C.A.; Maltha, Celia R.A.; Forlani, Giuseppe
Graphical abstract: Highlights: First total synthesis of Streptomyces sp. metabolites abenquines is reported. An efficient 3 step (41–61%) total synthesis of abenquines is described. Natural abenquines were synthetized by addition of amino acids to benzoquinone core. Natural abenquines and analogues were shown to have phytotoxic activity. Some abenquines are highly phytotoxic (IC50  < 10 μM) to cyanobacterium S. elongatus . Abstract: The first total synthesis of abenquines A, B2, C and D has been achieved in three steps starting from commercially available 2, 5-dimethoxyaniline, with overall yields of 41–61%. Four analogues bearing the amino acids d -valine (17 ), l -methionine (18 ), and glycine (19 ), and benzylamine (20 ), were also prepared in 45–72% yield. The inhibitory properties of these compounds were evaluated against the photoautotrophic growth of a model Synechococcus sp. strain. Abenquine C and its enantiomer were substantially ineffective, whereas all other abenquines significantly inhibited cell proliferation, with concentrations causing 50%-inhibition of algal growth ranging from 10 −5 to 10 −6  M.